Pengaruh Latihan Ladder Drill dan Harvard Step terhadap Frekuensi Langkah Kaki Dan Kecepatan Berlari pada Atlet Ekstrakurikuler Atletik SDN Sungai Jingah 5 - Maulana, Panji Rifqi; Rahmadi, Rahmadi; Shadiqin, AR. (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
The aim of this research was to determine the effect of ladder drill and Harvard step training on the frequency of footsteps and running speed of extracurricular athletics athletes at SDN Sungai Jingah 5 Banjarmasin. This research uses a quantitative type with the Pretest-Posttest Non-Equivalent Group Design method. The sample in this study were extracurricular athletic athletes at SDN Sungai Jingah 5 Banjarmasin. totaling 6 people, the sample was 6 athletes. The sampling technique was total sampling. The 6 athletes were given a test and measurement of running speed (Kanga's Escape) which was used as evidence for the initial test and final test to determine the athlete's stride frequency and running speed. The results of the initial test measurement of step frequency obtained an average value of 76.00 and running speed obtained an average value of 19.87. Then, ladder drill and Harvard step training was carried out for 16 meetings, there was an increase in the average step frequency of 68.66 and running speed of 18.54. Based on the conclusions of data analysis and hypothesis testing, the results of ladder drill and Harvard step training were found to increase the results of athlete's footstep frequency and running speed. extracurricular athletics at SDN Sungai Jingah 5 Banjarmasin Keywords: Ladder drill training, Harvard step training, Step Frequency, Running Speed